KERAGAAN PENDAPATAN USAHATANI JAGUNG MANIS (PIONIR) DAN JAGUNG HIBRIDA (BISI-2) DI DESA PUKDALE KECAMATAN KUPANG TIMUR KABUPATEN KUPANG. - Cheisia U.K .Tanaem,; Maria Bano; Chales Kapioru (Buletin Ilmiah Impas, 2020)
ABSTRACT Corn is one of the staple foodsthat is quite delighted especially for the NTT community. The local food of the NTT community besides rice is corn. This is evidenced by the diverse types of staple foods whose main raw material is corn. This study aims to find out how much revenue of sweet corn (Pioneer) and hybrid corn (Bisi-2) and to determine differences in income of sweet corn farming (Pioneer) and corn hybrid (Bisi-2) at Pukdale Village, East Kupang District, Kupang Regency. This research was conducted at Pukdale Village, East Kupang Subdistrict, Kupang Regency on the period from March to April 2019. To answer the goal, it can be analyzed using total corn farming income by total corn farming expenditure at one planting season, and the Gross Profit Margin approach to answer the second purpose. The results showed that the total income of hybrid maize and sweet corn in the research location wass Rp.49,425,000 with an average income per respondent of Rp.852,155 / season and the average income per hectare was Rp. 1,433,855 / season. While the total income of sweet corn farming obtained by respondent farmers is Rp.55,383,000 with an average income per respondent is Rp. 1,065,057 / season and the average income per Ha is Rp. 3,018,147 / season. The percentage of gross profit margin shows that the percentage of sweet corn of 20.63% is received within 2 months and while hybrid corn is 23.20% received within 3 months.